Impaired estrogen receptor action in the pathogenesis of the metabolic syndrome. (15th December 2015) - Hevener, Andrea L.; Clegg, Deborah J.; Mauvais-Jarvis, Franck
Abstract: Considering the current trends in life expectancy, women in the modern era are challenged with facing menopausal symptoms as well as heightened disease risk associated with increasing adiposity and metabolic dysfunction for up to three decades of life. Treatment strategies to combat metabolic dysfunction and associated pathologies have been hampered by our lack of understanding regarding the biological underpinnings of these clinical conditions and our incomplete understanding of the effects of estrogens and the tissue-specific functions and molecular actions of its receptors. In this review we provide evidence supporting a critical and protective role for the estrogen receptor α specific form in the maintenance of metabolic homeostasis and insulin sensitivity. Studies identifying the ER-regulated pathways required for disease prevention will lay the important foundation for the rational design of targeted therapeutics to improve women's health while limiting complications that have plagued traditional hormone replacement interventions. Highlights: Estadiol and ERs are critical in the regulation of energy balance and metabolism. Impaired ERα action promotes obesity and metabolic dysfunction in rodents. Tissue-specific actions of ERα control feeding, physical activity, insulin secretion and insulin sensitivity. ERα activates and represses target genes by a variety of complex signaling mechanisms. Sex hormone deficiency/inefficiency contributing to the pathogenesis of metabolic disease in women is a major medical challenge.